Fragmenting the Chieftain - catalogue : Late Bronze and Early Iron Age elite burials in the Low Countries - Vaart-Verschoof, Sasja van der (PALMA., 2017)
There is a cluster of Early Iron Age (800-500 BC) elite burials in the Low Countries in which bronze vessels, weaponry, horse-gear and wagons were interred as grave goods. Mostly imports from Central Europe, these objects are found brought together in varying configurations in cremation burials generally known as chieftains' graves or princely burials. In terms of grave goods they resemble the _Fürstengräber_ of the Hallstatt Culture of Central Europe, with famous Dutch and Belgian examples being the Chieftain's grave of Oss, the wagon-grave of Wijchen and the elite cemetery of Court-St-Etienn.